Keanekaragaman Bivalvia pada Ekosistem Padang Lamun di Perairan Pantai Kelurahan Mafututu Kecamatan Tidore Timur Kota Tidore Kepulauan - Hayatudin, Fahima; Damsiki, Nuraini Adung; Ahmad, Muhammad Ali (Jurnal Ilmiah Wahana Pendidikan, 2026)
Bivalves are organisms that belong to the phylum Mollusca, which are generally found and live in intertidal areas. The coastal waters of Kelurahan Mafututu Tidore Timur District Tidore Islands City, have the potential for a rich diversity of bivalves in the seagrass ecosystem can serve as an indicatior to dscribe the condition of the waters. This study aims to determine the diversity of bivalves in the seagrass ecosystem of coastal waters of Kelurahan Mafututu, Tidore Timur District Tidore Islands city. The research was conducted in october 2025 at tow observation stations located in the Majui and Tasuma. The sampling mothod used was a quantitative descriptive method with a transect and 1x1 m quadran thchnique, along with measurements of environmental parameter such as temperature, salinity, and pH. The results showed that at station 1, there were 7 species of bivalves with at total of 24 individuals, while at station 2 there were 4 species with a total of 19 individuals. The species found were Anadara sp, Anadara antiquate, Gafrarium tumidum, spondylus gaederopus, Corbicula fluminea, Danox faba and Callista chione Environmental parameters showed salinity of 30-33‰ temperature 28-29˚C, and pH values of 6, which are still withn optimal ranges for marine life. The Shannon wiener diversty index values H'= 1,56 at station 1 and H'=1,37 at station2 indicated a medium moderate level of diversity. The evenness indx values E= 0,86 at station 1 and E= 0,98 at station 2 show a high level of evenness among the spcies